Application of near-infrared fluorescence imaging in lingual lymph node screening and drainage pattern observation for tongue cancer - Zhu, Yaoping; Xiao, Tao; He, Yijia; Hong, Xiaowei; Zhou, Ting; Da, Mingjie; Ge, Sumeng; Xie, Diya; Wang, Zhiyong (Frontiers in Cell and Developmental Biology, 2022)
Objective: Lingual lymph node (LLN) metastasis should be considered an adverse prognostic factor and a vital sign of high primary tumor aggressiveness. However, detecting LLN metastasis is a crucial but often neglected part of diagnosis and surgical treatment planning. The study aims to identify the LLN by intraoperative near-infrared (NIR) fluorescence imaging with indocyanine green absorbed into human serum albumin (ICG: HSA) and describe the presence of lymphatic drainage pathways from the floor of the mouth in patients with tongue carcinoma. Materials and Methods: A total of 21 patients diagnosed with cT1-T4 Squamous cell carcinoma (SCC) of the mobile tongue margin and scheduled to undergo tumor resection and unilateral neck dissection were enrolled. 0.3mL ICG: HSA (500μM) was injected at 3 quadrants around the tumor except for the mucous membranes of the basilar region cavity after exposure of the neck in 21 patients. During the neck dissection, levels I, II, III, and IV were measured for fluorescence using the NIR fluorescence imaging system. Results: In all 21 patients, LLNs were detected in 4 patients and were identified as metastatic LLNs. The presence of lymphatic drainage pathways in the floor of the mouth could be demonstrated by the NIR fluorescence imaging system. For patients who received peritumoral injection of ICG: HSA, the mean fluorescence intensity (MFI) of metastatic LNs (178.4, average) was higher than that of non-metastatic LNs (132.0, average) (p<0.05). Conclusions: NIR fluorescence imaging with ICG: HSA could be used for intraoperative identification of the LLN and assist in the determination of metastatic lymph nodes for tongue carcinoma patients. Also, this finding shows the feasibility of NIR fluorescence imaging for defining regional lymphatic drainage pathways in the head and neck.